ANALISIS KETIDAKLANGSUNGAN EKSPRESI ANTOLOGI PUISI DOA UNTUK ANAK CUCU KARYA WILLYBRORDUS SURENDRA BHAWANA RENDRA BROTOATMOJO - Thoyib Thoyib (LPPM UNISDA, 2020)
The purpose of research include five things: the expression indirect include; Second, Reading of heuristics and reading hermeneutic, third, matrices, models and variants, fourth,hipogram (hypogram).in ontology poetry Doa untukAnakCucu by Willybrordus Surendra Bhawana Rendra Brotoatmojo. The research approach used is semiotic, that is studying the indirect expression to poetry by way of linguistic influence the meaning of a literary work as a whole and the effects on the reader. Data collection techniques using literature techniques, see and record.The data analysis technique that analyzes three grooves flowing with concurrent activities. That is; data reduction, data presentation, drawing contents in poetry. Methods of data analysis used in this study is a semiotic method, and approach indirect expression.The conclusions of this research consists of four things. First, the expression indirect include; Second, Reading of heuristics and reading hermeneutic, third, matrices, models and variants, fourth,hipogram (hypogram).